Playing Futsall Development Based on Model Variations - Marlina, Yeni; Zahara, Zahara; Syamsulrizal, Syamsulrizal; Iqbal, Muhammad (INSPIRETECH GLOBAL INSIGHT & DPE Universitas Pahlawan, 2023)
The purpose of the study. Universitas Syiah Kuala students who attended the Futsal TP course numbered one hundred and fifty people. And researchers determine the sample between forty five to fifty people. Materials and methods. The steps are adapted from the book